Comparative Antigenicity and Pathogenicity of Two Distinct Genotypes of Highly Pathogenic Avian Influenza Viruses (H5N8) From Wild Birds in China, 2020–2021 - Jiang, Wenming; Liu, Shuo; Yin, Xin; Li, Zhixin; Lan, Zouran; Xire, Luosong; Wang, Zhongbing; Xie, Yinqian; Peng, Cheng; Li, Jinping; Hou, Guangyu; Yu, Xiaohui; et al. (Frontiers in Microbiology, 2022)
To date, there have been three epidemic waves of H5N8 avian influenza worldwide. The current third epidemic wave began in October 2020 and has expanded to at least 46 countries. Active and passive surveillance were conducted to monitor H5N8 viruses from wild birds in China. Genetic analysis of 10 H5N8 viruses isolated from wild birds identified two different genotypes. Animal challenge experiments indicated that the H5N8 isolates are highly pathogenic in chickens, mildly pathogenic in ducks, while pathogenicity varied in Balb/c mice. Moreover, there were significant differences in antigenicity as compared to Re-11 vaccine strain and vaccinated chickens were not completely protected against challenge with the high dose of H5N8 virus. With the use of the new matched vaccine and increased poultry immune density, surveillance should be intensified to monitor the emergence of mutant strains and potential worldwide spread via wild birds.